The Effect of Antiepileptic Drug Therapy on Bone Metabolism and its Relationship with Vitamin D Receptor Gene - Çay, Özlem Özcanlı; Serin, Hepsen Mine; Koç, Zehra Pınar; Erol, Deniz; Yılmaz, Erdal (My University, 2019)
Objective: The relationship between antiepileptic drugs and bone health and also the geneticaspect of this relationship is not clear and has been investigated in recent years. The aim of this study wasto determine the effects of different antiepileptic drugs (AEDs) on bone mineral density results in longterm follow up and to evaluate the relationship with the vitamin D profile (Bsml mutation) of the patients. Material and Methods: Eighty ambulatory patients (21 male, 59 female; mean age: 9.1±3.85 years)were included in the study. The patients were divided into four groups; Group 1 (levetiracetam), Group2 (Carbamazepine), Group 3 (Valproic acid) and Group 4 (control). The plasma calcium, phosphorus,parathyroid hormone, alkaline phosphatase, vitamin D levels and bone mineral density values of femurand spine (L1-4) were compared. The patients were divided into two groups according to vitamin D receptor genes as the patients with Bsml mutations and without (wild type) Bsml mutations. Results: Thedifference between bone mineral density, Z score, phosphorus, parathyroid hormone, alkaline phosphatase and vitamin D levels of the patients in all four groups was not statistically significant. The phosphorus, parathyroid hormone, alkaline phosphatase and vitamin D levels and bone mineral density andZ score results of the patients with and without Bsml mutations were not significantly different. Conclusion: In this cross-sectional analysis, we found that the bone mineral status of the patients receivingdifferent AEDs for a long time (> 2 years) was not significantly different. There was also no loss of bonemineral content in the patient group when compared with age-appropriate controls. According to theresults of this study, Bsml polymorphism is not determinant in the progression of bone mineral loss.
Keywords: Endokrinoloji ve Metabolizma; Genel ve Dahili Tıp; Pediatri